Chapter Filosofia e dibattito. Le Meditazioni Cartesiane come esempio di deliberazione filosofica - Gabrielli, Caterina (Communication and Philosophical Cultures. Researches and Instruments, 2021)
This essay relates the content of an educational experience that applies the methodology of debate to the closer examination of an argumentative philosophical text, in the form of a deliberation with oneself. The text in question is Descartes' Meditations on First Philosophy, specifically the first, the second, the sixth meditation and respective Objections. The class involved in the activity is the IV B of the Liceo classico Alessandro Manzoni in Lecco.